New Perspectives From Unstructured Interviews: Young Women, Gender, and Sexuality on the Isle of Sheppey in 1980. (November 2016) - Sutcliffe-Braithwaite, Florence
In the early 1980s, Ray Pahl, a sociologist at the University of Kent, and PhD student Claire Wallace conducted interviews examining young people's experiences of growing up, work, and unemployment on the Isle of Sheppey; these interviews are now deposited at the University of Essex, and this article examines how historians and others might reuse them to interrogate other subjects. The article examines one working-class young woman's ideas about gender and sexuality in the early 1980s, using the Listening Guide method developed by psychologist Carol Gilligan to probe the individual subjectivity and emotion, as well as the cultural discourses at play in this interview. The interviewee was a young woman who was involved in a culture of casual sex with men "on the ships, " and the article focuses on how she saw the exchanges of money, drink, and gifts between them and herself, and how she avoided seeing her actions as "prostitution." The analysis shows how in a particular locality in the early 1980s, a particular subculture could allow some young women to sidestep the dominant codes governing young, working-class women's sexuality and go "on the ships" without seeing this as marking them as "prostitutes"' or any related category. Thus, the article troubles the ontology of "prostitution" as a category. It also suggests how we can use a single individual's narrative to offer a broader account of cultures or subcultures, by starting with the individual and examining how one subjectivity navigated and interacted with broader cultural discourses. Finally, this article also offers suggestions about some of the methodological and ethical issues with reusing archived sociological data but argues that it holds rich possibilities.